Bilateral Pulmonary Hydatid Cyst in an 11 Year Boy: A Case Report - Kumar, Maoulik; Singh, Lokesh; debi, Uma; Choudhury, Shayeri Roy; Bhatia, Vikas (Archives of Clinical and Medical Case Reports, 2020)
Hydatid disease, a zoonosis, most commonly caused by the parasite Echinococcus granulosus. Hydatid cysts can occur in any organ of the human body, liver followed by lung being the most common location, while in children lung involvement is more common than liver. Cough is usually the most common presenting symptoms. Other common symptoms include shortness of breath, chest pain, fever, hemoptysis or it may be asymptomatic. Pulmonary hydatid cysts grow faster as compared to those in other organs as lung tissue is elastic and compliant. Chest radiograph and Computed tomography(CT) are the most commonly used imaging modality for diagnosis of pulmonary hydatid cyst. Contrast enhanced CT is very valuable for evaluating hydatid especially complicated cyst.